2010
DOI: 10.4314/jolte.v2i1.52011
|View full text |Cite
|
Sign up to set email alerts
|

The role of visibility and career advancement of women in Kenya

Abstract: The purpose of this study was to investigate whether women employees are visible in their organizations in Kenya. The study was a cross-sectional survey carried out among women employees of the Federation of Kenya Employers (FKE) member organizations. Stratified and random sampling was used to select a sample of 400 women employees. Data were collected using a self administered questionnaire and analysed using both quantitative and qualitative techniques. The results indicate that the visibility of women in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to Cooper, (14) reductions in job security leads to lower levels of commitment and therefore job satisfaction, organizational instability and ongoing change with potentially negative consequences undermine job security. Comparing to finding of previous study, majority of the respondents were neutral with their job security (12).Our research finding indicated that only 80 (34%) of the employees at Misurata medical center were satisfied with their monthly salary. This finding is consistent with finding of previous study (12).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…According to Cooper, (14) reductions in job security leads to lower levels of commitment and therefore job satisfaction, organizational instability and ongoing change with potentially negative consequences undermine job security. Comparing to finding of previous study, majority of the respondents were neutral with their job security (12).Our research finding indicated that only 80 (34%) of the employees at Misurata medical center were satisfied with their monthly salary. This finding is consistent with finding of previous study (12).…”
Section: Discussioncontrasting
confidence: 73%
“…Comparing to finding of previous study, majority of the respondents were neutral with their job security (12).Our research finding indicated that only 80 (34%) of the employees at Misurata medical center were satisfied with their monthly salary. This finding is consistent with finding of previous study (12). However, Armstrong indicated that notes that, money, in any form of pay, is the most obvious form of extrinsic reward and it "provides the carrot remuneration that most people want."…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Moreover, ethical leaders can help improve employees' intrinsic motivation by applying fair treatment and caring about employees' personal needs and interests. In a hospitality context, it is important that the leaders take a flexible approach to rotate employees to their preferred team that fits their ability because job rotation has been identified as a predictor of intrinsic motivation (Linge, 2019). Meanwhile, entrepreneurial leaders should provide their employees with challenging goals as well as grant them autonomy to explore initiatives to fulfil such goals to promote employees' intrinsic motivation.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Igbaria and Baroudi (1995) investigated that women received less favourable chance for advancement in their organization as compared to male. To reduce barriers toward career advancement faced by female, Linge, VanRensburg, and Sikalieh (2010) recommended that women should increase their visibility with professional association, client's networks, peers and friends, which in turn enhanced their presence and career progress. Although, evaluating employee performance on work and comparing the difference between performance levels of gender, result in different approach for advancement.…”
mentioning
confidence: 99%